Lignocellulose-derived platform molecules: an introduction - Shinde, Suhas H.; Hengne, Amol; Rode, Chandrashekhar V. (Recent Advances in Development of Platform Chemicals, 2020)
Fossil feedstocks such as crude oil, natural gas, and coal are formed by natural anaerobic decomposition of buried organisms for a period of more than 650 million years. On the other hand, agrobiomass is quick to grow and becomes a renewable source of chemical and fuel production through processing in a biorefinery.
Keywords: Biomass; Biorefinery Cellulose; Lignocellulose Petrofinery; Platform molecules

Sustainable UV absorbing bio-plastic films by valorisation of humins and chitosan - Lucas, Nishita; Tambe, Snehal S.; Parate, Roopa; Hengne, Amol; Rode, C. V.; Athawale, Anjali A. (International Journal of Biological Macromolecules, 2025)
Humins, an inevitable bio-refinery waste by-product of sugar dehydration have been efficiently utilized for the first time for developing biodegradable thin films for UV shielding. The films were prepared from chitosan, and humins, a novel combination, aiming towards simultaneous utilization of marine and bio-refinery waste, rendering simple, effective, robust UV absorbing films. The structure-activity relationship of these films were elucidated with the help of different analytical techniques like X-ray diffraction, Fourier transform infrared spectroscopy, Thermogravimetric analysis, UV-vis spectroscopy, Atomic force microscopy, Scanning electron microscopy, Tensile testing, Contact angle measurements and water absorption studies. Intrinsic biodegradability was studied using fungi i.e. Aspergillus niger. Different feedstocks (corncob, rice husk, glucose and xylose) were explored for generating humins. Amongst them, humins derived from xylose were utilized for the preparation of the bio-plastic films of chitosan. The results revealed that, addition of 5.0 % humins was observed to be an optimum concentration yielding films with excellent UV absorption, mechanical properties, and biodegradability. The current work is in perfect alignment with sustainability and green chemistry as it ameliorates waste valorization (lignocellulosic and marine altogether). Further, its innovation stems from the first-hand use of humins for UV absorption, novel combination of biopolymers, use of green raw materials.
Keywords: biodegradable; Chitosan; Humins; Thin films; UV absorption; Waste valorization